Neutrally Floating Objects of Density ½ in Three Dimensions. Issue 3 (16th November 2012) - Várkonyi, P. L.
<x xml:space="preserve">Abstract</x> This paper is concerned with the Floating Body Problem of S. Ulam: the existence of objects other than the sphere, which can float in liquid in any orientation. Despite recent results of F. Wegner pointing towards an affirmative answer, a full proof of their existence is still unavailable. For objects with cylindrical symmetry and density 1/2, the conditions of neutral floating are formulated as an initial value problem, for which a unique solution is predicted in certain cases by a suitable generalization of the Picard–Lindelöf theorem. Numerical integration of the initial value problem provides a rich variety of neutrally floating shapes.